MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI KEGIATAN MENGGUNTING PADA ANAK KELOMPOK B DI TK DAHLIA 4 ANGGANA - Waryanti; Arbayah; Sjamsir, Hasbi (Manajemen Pendidikan Program Doktor, 2023)
Based on the results of observations or observations that the author has been doing, also based on interviews with several children and exchanges with fellow teachers in early childhood education institutions that the author manages, in general, fine motor skills have not been developed optimally. For example, in the paper-cutting activity of 17 students, there are only 6 students or 35% of students who are able to cut well and there are still 75% of students or 11 students who are not able to cut well. Therefore, the author conducted a study on